Psychometric Properties of a French Version of the Perceived Motor Competence in Childhood Questionnaire - Maïano, Christophe (Percept Mot Skills, 2021)
In this study, we examined the psychometric properties of a French version of the Perceived Motor Competence in Childhood (PMC-C) questionnaire. The participants were 219 French-speaking children (aged 5-12 years), recruited from elementary schools in the Canadian Province of Quebec. Results supported the validity and reliability of a second-order confirmatory factor analytic (CFA) model, including one higher-order factor. Additional analyses supported the complete measurement invariance of the first- and second-order factor structure across sex and indicated no differential item functioning or latent mean differences in PMC-C factors as a function of selected predictors (i.e., age, body mass-index and physical activity/sport involvement). Thus, this French version of the PMC-C has satisfactory psychometric properties (i.e., factor validity and reliability, measurement invariance and differential item functioning) and can be used to assess French-speaking children’s perceived motor competence.